PHILOSOPHICAL-METHODOLOGICAL ANALYSIS OF MODERN TEACHING SYSTEM (Web of Teachers: Inderscience Research, 2023)
In this article, the main goal of the state policy in the field of education is to increase the convenience and quality of education that meets the needs of society and each of its citizens. socio-philosophical analysis of the mechanisms of formation of intellectual culture.